Embrioni nel tempo profondo Il registro paleontologico dell'evoluzione biologica - Sánchez, Marcelo (Studi e saggi, 2014)
How can we put together the study of genes, embryos and fossils? Can fossils demonstrate evolutionary changes in the reproductive modes? How have changes in the chemical composition of the oceans influenced the development of sea organisms? What does the micro-structure of bones and teeth reveal about reaching maturity, longevity and changes in the growth cycles of extinct organisms? «Embrioni nel tempo profondo» discusses these and other topics by offering a critical synthesis of concepts from comparative anatomy, ecology and developmental genetics. This book illustrates how fossils can provide information not only about the anatomy of adults, but also about the life history of individuals at different times in their lives. The transformations occurring during the life of an organism and the mechanisms enabling them, one of the main topics of modern biology, are discussed in a comparative and integrated way, revealing that fossils offer a unique insight into the central ideas of evolution and development.